Adaptive Partnership Strategy between Private Islamic Vocational Schools and Business/Industry Enterprises in Preparing Competent Graduates: Dynamic Analysis and SWOT-Based Approach - Ramdhani, Muhammad Rendi; Iswan, Iswan; Husainah, Nazifah (PENANOMICS: International Journal of Economics, 2025)
This study aims to analyze adaptive partnership strategies between private Islamic Vocational High Schools (SMK) and the Business/Industry World (DU/DI) in improving the quality of vocational education graduates relevant to job market needs. Using a qualitative approach and a multi-case study design, the research was conducted at three leading private Islamic Vocational High Schools (SMK) in Bogor Regency: SMK Ibnu Aqil, SMK Muhammadiyah 1 Cileungsi, and SMK Amaliah 2 Ciawi. Data were collected through participant observation, in-depth interviews, and documentation studies, then analyzed using the Miles, Huberman, and Saldana models assisted by Nvivo software, as well as a SWOT approach. The results show that partnership dynamics are formed through the interaction of supporting factors such as active leadership, Islamic values, and industrial partner networks, as well as obstacles such as curriculum gaps, limited productive teachers, and minimal industrial investment. All three schools implemented adaptive strategies, such as integrating religious values, digitizing learning, and strengthening international partnerships. The SWOT analysis shows that private Islamic Vocational High Schools have significant internal strengths to capitalize on opportunities, although they also face various external threats. This study concludes the importance of strengthening strategies based on local context and Islamic values ​​to achieve sustainable vocational partnerships that are responsive to the demands of modern industry.